1986
DOI: 10.1152/ajpcell.1986.250.1.c90
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channel selectivity in mouse pancreatic B cells

Abstract: High-resistance microelectrodes were used to measure membrane potential changes in response to increased extracellular K+ concentration ([K+]o; or a test cation X+ such as Li+, Rb+, Cs+, NH+4) in B cells from mouse islets of Langerhans. In the absence of glucose, a sudden increase in [K+]o (or [X+]o), keeping the sum [Na+]o + [K+]o constant (or [Na+]o + [K+]o + [X+]o), induced a rapid depolarization of the membrane. The membrane potential changes were essentially unchanged in the presence of 20 mM tetraethylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…However, significant permeability (P) to Cs¤ of voltagedependent K¤ channels was also reported (PCsÏPK = 0·16, Hadley & Hume, 1990; PCsÏPK = 0·62, Rosario & Rojas, 1986; PCsÏPK = 0·11, Gay & Stanfield, 1978). In the present study, we showed a substantial degree of Cs¤ permeability through the IKr channel.…”
Section: Discussionsupporting
confidence: 72%
“…However, significant permeability (P) to Cs¤ of voltagedependent K¤ channels was also reported (PCsÏPK = 0·16, Hadley & Hume, 1990; PCsÏPK = 0·62, Rosario & Rojas, 1986; PCsÏPK = 0·11, Gay & Stanfield, 1978). In the present study, we showed a substantial degree of Cs¤ permeability through the IKr channel.…”
Section: Discussionsupporting
confidence: 72%
“…The pancreatic islets from the ob/ob strain of mice (Norwich colony, UK) have been shown to display subtle abnormalities in the membrane potential fluctuations stimulated by glucose and to be relatively insensitive to sulfonylureas [5,6]. We found that the pancreatic ~ cells from the same ob/ob strain of mice (Jackson Laboratory colony) have the 3 kinds of potassium channels characterized in normal rats, mice, humans and islet-derived cell lines.…”
Section: Discussionmentioning
confidence: 80%
“…Defects in the potassium permeability of some diabetic mouse models have been reported [3]. Membrane potential measurements in pancreatic islets from homozygous db/db (diabetic) and ob/ob (obese) mice show abnormalities in the response to glucose consistent with a defective potassium conductance [4][5][6].…”
Section: Introductionmentioning
confidence: 97%
“…This suggests a steady-state cell depolarization. The K+(ATP) channel may be somewhat permeable to NH4C1 in that, at rest, the B-cell membrane is estimated to be roughly 1/3 as permeable to NH2 as to K + (Rosario & Rojas, 1986a). Assuming (i) that NH~-acts as a permeant blocker of the K+(ATP) channel from the cytoplasmic surface of the membrane, as it does with the K+(Ca 2+) channel (see Tabcharani & Misler, 1989), and (ii) the K+(ATP) channel of the B cell, like the K+(Ca 2+) channel, behaves like a multi-ion channel where mutual repulsion between cations augments their traversal of the membrane, two predictions seem reasonable.…”
Section: Discussionmentioning
confidence: 99%